Remote sensing of soil salinity mapping: status and potential - Ayan Das; Bhattacharya, Bimal K.; Obi Reddy, G.P.; Bhaskar Narjary; Sharma, P.C.; Samar Attaher; Govind, Ajit; Chakraborty, Debashis (2023)
Soil salinization is a significant form of land degradation in agricultural areas. Remote sensing is a better way to assess soil salinity than traditional methods, as it provides non-destructive and repetitive informative assessment for monitoring and mapping soil salinity. Different sensors can identify soil salinity in remote sensing data through direct and indirect indicators. A Brief review of the major soil salinity mapping studies is presented here. This review aims to explore various indicators of soil salinity, evaluate the satellite sensors and methods employed for remote detection, monitoring, and mapping of soil salinity, and shed light on the key challenges that restrict the use of remote sensing for soil salinity mapping in drylands. Additionally, the paper will also examine the context of soil salinity in irrigated lands of Egypt.